2021
DOI: 10.1038/s41388-021-02040-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the wild-type KRAS allele promotes pancreatic cancer progression through functional activation of YAP1

Abstract: Human pancreatic ductal adenocarcinoma (PDAC) harboring one KRAS mutant allele often displays increasing genomic loss of the remaining wild-type (WT) allele (known as LOH at KRAS ) as tumors progress to metastasis, yet the molecular ramification of this WT allelic loss is unknown. In this study, we showed that the restoration of WT KRAS expression in human PDAC cell lines with LOH at KRAS significantly attenuated the malignancy of PDAC cells both in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Hippo Signaling Pathway. Oncogenes often promote tumor progression by regulating the signaling pathways [12,13]. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that TOP2A was associated to cell cycle, progesterone-mediated oocyte maturation, p53 signaling pathway, and Hippo signaling pathway (Figure 5(a)).…”
Section: Top2a Affecting Hcc Tumor Progression Throughmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippo Signaling Pathway. Oncogenes often promote tumor progression by regulating the signaling pathways [12,13]. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that TOP2A was associated to cell cycle, progesterone-mediated oocyte maturation, p53 signaling pathway, and Hippo signaling pathway (Figure 5(a)).…”
Section: Top2a Affecting Hcc Tumor Progression Throughmentioning
confidence: 99%
“…Dysregulation of the Hippo signaling pathway promotes cancer progression [ 12 , 13 ]. Moya et al [ 14 ] found that the activity of yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) in tumors was linked to the progression of liver tumors.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on two 14-3-3 proteins, 14-3-3 zeta and 14-3-3 gamma, and two protein phosphatases, protein phosphatase 1 catalytic subunit alpha (PPP1CA) and PP2Ac (Fig. 5E), because they have been reported to participate in the regulation of YAP in multiple tissues (Hu et al, 2017; Meng et al, 2016; Qi et al, 2015; Schlegelmilch et al, 2011; Sun et al, 2021; Yan et al, 2021). It is known that the turnover of YAP is regulated through its phosphorylation and ubiquitination in a 14-3-3 dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between YAP and the RAF/MEK/ERK cascade was discovered by genetic screens, which showed that the inhibitory combination of RAF or MEK with YAP has increased efficacy not only in BRAF-mutant cancers but also in KRAS-mutant cancers (67). In a KRAS G12C mutant PDAC model, inhibition of YAP1 improves the efficacy of KRAS blockade (68). c-MYC is another oncogenic transcription factor being involved in crucial processes such as metabolic reprograming, extracellular matrix remodeling, inflammation, and regulation of a variety of malignant features in cancer (69).…”
Section: Non-genetic Adaptive Resistance Kras G12c Inhibition: Symbio...mentioning
confidence: 99%
“…The relationship between YAP and the RAF/MEK/ERK cascade was discovered by genetic screens, which showed that the inhibitory combination of RAF or MEK with YAP has increased efficacy not only in BRAF-mutant cancers but also in KRAS-mutant cancers ( 67 ). In a KRAS G12C mutant PDAC model, inhibition of YAP1 improves the efficacy of KRAS blockade ( 68 ).…”
Section: Non-genetic Adaptive Resistance Kras G12c ...mentioning
confidence: 99%